Drgania Wymuszone Belki i Płyty na Podłożu Odkształcalnym w Zakresie Lepkosprężystym pod Obciążeniem Ruchomym - Szcześniak, W. (Engineering Transactions, 1972)
The paper presents the solution of the problem of vibrations of a visco-elastic beam and plate resting on a deformable foundation; the vibrations are forced by a weightless load moving at a constant velocity. The problem is solved by means of the orthogonalization method, the eigenfunctions of the boundary value problem being used. From the analysis it follows that the critical velocity of the load depends both on the internal dumping (internal friction) and on the phenomenological dumping within the foundation; the both dumpling phenomena are shown to have a significant influence on the vibration amplitude.